Avid (18)F-FDG Uptake in Idiopathic Tumoral Calcinosis Mimicking Lymph Node Metastasis - Strandberg, Jesper (Diagnostics (Basel), 2017)
Tumoral calcinosis is a benign condition characterized by periarticular calcified lesions that is frequently observed in patients with chronic renal failure. Tumoral calcinosis often presents with subcutaneous masses and joint swelling. We present a case of tumoral calcinosis with dramatically increased (18)F-fluoro-2-deoxy-d-glucose ((18)F-FDG) uptake on positron emission tomography/computed tomography (PET/CT) that mimicked lymphoma or lymph node metastases.